2022
DOI: 10.3390/pharmaceutics14030652
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Peptide Hydrogels as a Combination Drug Delivery System for Cancer Treatment

Abstract: Conventional antitumor chemotherapeutics generally have shortcomings in terms of dissolubility, selectivity and drug action time, and it has been difficult to achieve high antitumor efficacy with single-drug therapy. At present, combination therapy with two or more drugs is widely used in the treatment of cancer, but a shortcoming is that the drugs do not reach the target at the same time, resulting in a reduction in efficacy. Therefore, it is necessary to design a carrier that can release two drugs at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…However, in recent years, as tumor immunotherapy strategies continue to improve, it has been reported that immunotherapy could be e ective in LUSC, regardless of the PD-L1 expression and TMB levels [3][4][5][6][7]. At present, with the advent of more and more antitumor drugs, methods to improve the e ect of antitumor drugs, especially immunotherapy, have also gratifying results, such as using nanotechnology as a carrier [8][9][10][11][12]. erefore, identifying biomarkers that could accurately predict patient prognosis and e cacy of immunotherapy is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, as tumor immunotherapy strategies continue to improve, it has been reported that immunotherapy could be e ective in LUSC, regardless of the PD-L1 expression and TMB levels [3][4][5][6][7]. At present, with the advent of more and more antitumor drugs, methods to improve the e ect of antitumor drugs, especially immunotherapy, have also gratifying results, such as using nanotechnology as a carrier [8][9][10][11][12]. erefore, identifying biomarkers that could accurately predict patient prognosis and e cacy of immunotherapy is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported the synthesis of an injectable and pH-responsive oligopeptide hydrogel for the co-delivery and controlled release of two therapeutic drugs, gemcitabine (GEM) and paclitaxel (PTX), at the tumor site [ 77 ]. They reported the optimal concentration of the peptide for hydrogelation and then studied the in vitro pH-dependent release of this drug delivery platform.…”
Section: Biomedical Applications Of Peptide-based Hydrogelsmentioning
confidence: 99%
“…5) NDSs can achieve controlled release of drugs. Namely engineered stimuli-responsive nanomaterials enable precise drug delivery and controlled release under the influence of endogenous or exogenous stimuli ( Zhu G. et al, 2017 ; Bhushan et al, 2017 ; Liu et al, 2017 ; Cao et al, 2020 ; Zhu et al, 2020 ; Gote et al, 2021 ; Li et al, 2021 ; Yang et al, 2021 ; Liu et al, 2022 ).…”
Section: Nanoparticulate Delivery Systemsmentioning
confidence: 99%